3D printing of high surface area ceramic honeycombs substrates and comparative evaluation for treatment of sewage in Phytorid application. (October 2020) - Biswas, Papiya; Mamatha, Sirisala; Varghese, Kezil; Johnson, Roy; Vijay, Ritesh; Kumar, Rakesh
Graphical abstract: Abstract: Substrates properties play an important role in immobilization of bio-organisms and hence in optimizing design of the bioreactor to maximize the performance. Highly flexible 3D printing process based on virtual Computer Aided Design (CAD) is used for producing honeycomb substrates with desired properties. Clay based honeycomb with square, triangular and hexagonal configurations are 3D printed in order to achieve substrates with pre-designed geometrical surface areas. Laboratory reactors were fabricated with engineered properties using 3D printed honeycombs and a combination of honeycombs and commonly used stones for performance evaluation. Additionally, reactor based on commonly used gravel stones also fabricated for sake of comparison of performance. In order to elucidate the performance, sewage mix was fed into the reactors and the space velocity of all the three reactors were maintained at 0.041 h −1 . The sewage before and after treatment was tested for the performance markers such as pH, TSS, BOD and COD. Treated water met the stipulated standards prescribed by American Public Health Association with respect to all parameters studied. Though the difference in the performance of the reactors was marginal, with honeycombs a substantial reduction in the weight of the reactor can be accrued along with high mass transfer due to low pressure drop which can be attributed to the inherent higher surface to volume ratio. Further, by engineering the surface porosity of the honeycombs, it is possible reduce TSS as demonstrated in this study. These advantages offer flexibility in scaling up the reactors for larger capacities for de-centralized requirements.